C-X-C-Chemokine-Receptor-Type-4 Inhibitor AMD3100 Attenuates Pulmonary Inflammation and Fibrosis in Silicotic Mice - Sun Q; Tao X; Li B; Cao H; Chen H; Zou Y; Tao H; Mu M; Wang W; Xu K (Dove Medical Press, 2022)
Qixian Sun,1 Xinrong Tao,1- 4 Bing Li,1 Hangbing Cao,1 Haoming Chen,1 Yuanjie Zou,1 Huihui Tao,1- 4 Min Mu,1- 4 Wenyang Wang,1 Keyi Xu1- 4 1Center for Medical Research, Medical School, Anhui University of Science and Technology, Huainan, People's Republic of China; 2Key Laboratory of Industrial Dust Control and Occupational Health, Ministry of Education, Anhui University of Science and Technology, Huainan, People's Republic of China; 3Key Laboratory of Industrial Dust Deep Reduction and Occupational Health and Safety, Anhui Higher Education Institutes, Anhui University of Science and Technology, Huainan, People's Republic of China; 4Engineering Laboratory of Occupational Safety and Health, Anhui Province, Anhui University of Science and Technology, Huainan, People's Republic of ChinaCorrespondence: Xinrong Tao, Medical School, Anhui University of Science and Technology, Huainan, People's Republic of China, Email xrtao1116@hotmail.comBackground: Silicosis is a severe pulmonary disease caused by inhaling dust containing crystalline silica. The progression of silicosis to pulmonary fibrosis is usually unavoidable. Recent studies have revealed positivity for the overexpression of C-X-C chemokine receptor type 4 (CXCR4) in pulmonary fibrosis and shown that the CXCR4 inhibitor AMD3100 attenuated pulmonary fibrosis after bleomycin challenge and paraquat exposure. However, it is unclear whether AMD3100 reduces crystalline silica-induced pulmonary fibrosis.Methods: C57BL/6 male mice were instilled intranasally with a single dose of crystalline silica (12 mg/60 μL) to establish an acute silicosis mouse model. Twelve hours later, the mice were injected intraperitoneally with 5 mg/kg AMD3100 or control solution. Then, the mice were weighed daily and sacrificed on day 7, 14, or 28 to collect lung tissue and peripheral blood. Western blotting was also applied to determine the level of CXCR4, while different histological techniques were used to assess pulmonary inflammation and fibrosis. In addition, the level of B cells in peripheral blood was measured by flow cytometry.Results: CXCR4 and its ligand CXCL12 were upregulated in the lung tissues of crystalline silica-exposed mice. Blocking CXCR4 with AMD3100 suppressed the upregulation of CXCR4/CXCL12, reduced the severity of lung injury, and prevented weight loss. It also inhibited neutrophil infiltration at inflammatory sites and neutrophil extracellular trap formation, as well as reduced B-lymphocyte aggregates in the lung. Additionally, it decreased the recruitment of circulating fibrocytes (CD45+collagen I+CXCR4+) to the lung and the deposition of collagen I and α-smooth muscle actin in lung tissue. AMD3100 also increased the level of B cells in peripheral blood, preventing circulating B cells from migrating to the injured lungs.Conclusion: Blocking CXCR4 with AMD3100 delays pulmonary inflammation and fibrosis in a silicosis mouse model, suggesting the potential of AMD3100 as a drug for treating silicosis.Keywords: CXCR4, silicosis, pulmonary fibrosis, inflammation, AMD3100, mice